Use of paired words in multi-system languages (Eurasian Journal of Philology Science and Education, 2018)
This article deals with variousscientific approaches and classifications of paired words in multi-system languages. The purpose of this work is a comprehensive study of paired words, their structural features, formation, use and many other related issues. As well as study the language system for the purpose of revealing the semantic, communicative, categorical status of the category of uncertain multiplicity and singularity; classify a subcategory of the quantitative category and analyze the internal structural feature of the category of indefinite multiplicity and singularity; analyze the transmission of uncertain multiplicity in Kazakh, German and English languages by phraseological phrases and consider their use in literary works.The examinedworksallowed us to define the main directions, ideas and notionin the study of this conception and to determine the prospects for further research.